Development of a framework for the transfer of quality management to Thai industry - Nagswasdi, Montalee (1998)
Due to the rapid changes in manufacturing environment, management innovation has been of heightened interest for industrial practitioners. All over the world, organizations are searching for the best approaches that allow them to sustain growth and competitiveness. Of equal importance is the adoption and transfer of management practices that have been successfully applied in various environments.